PEMIDANAAN KEBIRI TERHADAP PELAKU KEJAHATAN SEKSUAL KEPADA ANAK PERSPEKTIF HAK ASASI MANUSIA DAN HUKUM ISLAM - Ahmad Jamaludin; Sayid Mohammad Rifqi Noval (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2020)
Sexual crimes in Indonesia have become increasingly worrying, especially against children, efforts to protect child victims by the government with Perpu No.1 of 2016 which has been passed into Law Number 17 of 2017 concerning child protection. This Perpu provides for additional regulations with castration for sexual crimes against children. The making of this policy was tinged with pros and cons because it was not in accordance with the objectives of punishment and Islamic law. The research method used is normative juridical with quantitative analysis. The purpose of this research is to see the view of the purpose of the punishment of chemical castration which is released to perpetrators of sexual crimes and to see and explain the Islamic legal views of the act of castration. The results of this study are First, the implementation of castration is an act of violence and contrary to the 1945 Constitution, namely Article 28 G paragraph 2 and Article 33 paragraph 1 of Law No. 39 of 1999 concerning Human Rights. Both Islamic Laws do not speak in writing about castration. The castration penalty stipulated in Law 17 of 2016 is a prohibition which is categorized as a punishment for takzir, because it is made by the state or leaders to overcome sexual crimes against children. The conclusion of this research is that first, castration punishment is a punishment that can violate human rights. Second, castration punishment in Islam is categorized as takzir punishment.